- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,812

Solve the equation $\sqrt{1+\sqrt{1-x^2}}(\sqrt{(1+x)^3}-\sqrt{(1-x)^3}=2+\sqrt{1-x^2}$.

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,812

Solve the equation $\sqrt{1+\sqrt{1-x^2}}(\sqrt{(1+x)^3}-\sqrt{(1-x)^3}=2+\sqrt{1-x^2}$.

- Nov 26, 2013

- 733

$\sqrt{1+ab}\left ( a^3 - b^3 \right ) = 2 + ab$

$\sqrt{1+ab}\left ( a - b \right )(a^2+b^2+ab) = 2 + ab$

$\sqrt{1+ab}\left ( a - b \right ) = 1$ - because $a^2+b^2 = 2$.

Squaring yields:

$(1+ab)\left ( a^2 + b^2-2ab \right ) = 1$

or

$2(1+ab)(1-ab)= 1$

or $(ab)^2 = \frac{1}{2}$

- hence $1-x^2 =\frac{1}{2}$ or $x = \pm\frac{1}{\sqrt{2}}$.

- Thread starter
- Admin
- #3